ChemInform Abstract: Pd(II)‐Catalyzed C(sp2)—H Carbonylation of Biaryl‐2‐amine: Synthesis of Phenanthridinones. Issue 48 (26th November 2013) - Liang, Zunjun; Zhang, Jitan; Liu, Zhanxiang; Wang, Kai; Zhang, Yuhong
Abstract A novel protocol for amine directed Pd‐catalyzed carbonylation of biaryls (I) is developed.